Case report: Giant cystic ileal gastrointestinal stromal tumor with an atypical intratumoral abscess - Chen, Linguang; Gu, Jiannan; Zhang, Xuejun; Yu, Aijun (Frontiers in Surgery, 2023)
Gastrointestinal stromal tumors (GISTs) are typically solid, sometimes with small cystic areas, but rarely manifest as predominantly cystic neoplasms. In addition, cystic intestinal GISTs with intratumoral abscess formation are rare. Here, we present the case of a 49-year-old male patient with a history of frequent and urgent urination for 2 weeks. Radiologic studies revealed a large cystic mass in the lower abdomen. The patient underwent abdominal laparotomy, which revealed a large cystic mass arising from the distal ileum invading the sigmoid mesocolon and apex vesicae. Partial resection of the ileum along with the tumor and the adjacent bladder was performed. Macroscopic examination revealed that the cystic mass contained a large amount of foul-smelling pus and a tumor- bowel fistula. The final pathology revealed an abdominal stromal tumor. Postoperative recovery was uneventful, and adjuvant imatinib mesylate 400 mg was administered daily. No tumor recurrence or metastasis was observed during the 9-month follow-up period